Wizja moralnego porządku społeczeństwa na łamach „Przeglądu Tygodniowego” i „Przeglądu Katolickiego” (1864-1880) - Markiewicz, Grzegorz (Acta Universitatis Lodziensis. Folia Historica, 1999)
This article is devoted to the part of the discussion, that took place in the press of the Kingdom of Poland just after the January Uprising (1863-1864) had collapsed. The great changes which occurred in that period in social, economic and political life of Poland forced the Polish publicists to analyse the past, presence and perspectives for the future. The disputes on the ways of the reconstruction of the economic and social system of the country were accompanied by the parallel debates on the necessity to reshape the hierarchy of commonly accepted values and social consciousness of the Poles. „Przegląd Tygodniowy” and „Przegląd Katolicki” were both weeklies still each one represented quite a different outlook and promoted different system of values. The first one was connected with the positivist philosophy the second one was a catholic weekly. Each one represented different social groups as well: „Przegląd Tygodniowy” was connected with an informal group of radical intelligentsia, „Przegląd Katolicki” reflected the point of view of a very formal institution, namely - the Catholic Church. Both weeklies shared a common will to shape the public opinion and the mentality of the society. Both of them paid much attention to the system of values and social rules that were observed in those times that means to all of that which in the wider sense is called an ethos and in the narrow one the morality and refers to the spiritual sphere of human and social activity that influences the deeds of people. „Przegląd Tygodniowy” considered the changes in the common consciousness of the society to be the crucial ones for the successful social and economic development. „Przegląd Katolicki” on its side stressed the importance of the consciousness as the base of a social order and subordinated to it all the other areas of the human activity. For both weeklies the question of morality played a crucial role in the shaping of the image of the society created by their publicists.